2012
DOI: 10.1093/molbev/mss262
|View full text |Cite
|
Sign up to set email alerts
|

Human MicroRNAs Originated from Two Periods at Accelerated Rates in Mammalian Evolution

Abstract: MicroRNAs (miRNAs) are short, noncoding RNAs that modulate genes posttranscriptionally. Frequent gains and losses of miRNA genes have been reported to occur during evolution. However, little is known systematically about the periods of evolutionary origin of the present miRNA gene repertoire of an extant mammalian species. Thus, in this study, we estimated the evolutionary periods during which each of 1,433 present human miRNA genes originated within 15 periods, from human to platypus–human common ancestral br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 36 publications
(47 reference statements)
9
47
3
1
Order By: Relevance
“…63,64 Furthermore, the evolution of the complementary strand of miR214 into a functional processed miR, miR3120, reveals a new type of miR emergence by complementarity with the mirrored miR gene. Altogether, the evolution of the miR199-214 cluster provides various examples of duplication, retention, and lineage-specific loss or gain of miR sequences illustrating the range of processes in miR gene evolution.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Furthermore, the evolution of the complementary strand of miR214 into a functional processed miR, miR3120, reveals a new type of miR emergence by complementarity with the mirrored miR gene. Altogether, the evolution of the miR199-214 cluster provides various examples of duplication, retention, and lineage-specific loss or gain of miR sequences illustrating the range of processes in miR gene evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammal lineage, miRNAs seemed to have evolved rapidly, with some newborn miRNAs getting lost while many others with increased expression were conserved in the nervous system, thus displaying robustness in the gene networks (Meunier et al, 2013). Such rapid evolutionary rates have also been observed during the early evolution of marsupials and the late evolutionary history of humans (Iwama et al, 2013). All of these findings indicate that miRNAs are linked to phenotype formation and thus species evolution.…”
Section: Introductionmentioning
confidence: 86%
“…This suggests that differences in expression levels between young and old miRNAs may have been decreased, and that young miRNAs could have already performed important functions in humans. Iwama et al (2013) reported an increase in miRNA expression that was specific to the initial hominoid lineage. Therefore, fast-evolving miRNAs in humans may have been subjected to high, positive selection pressure, which may not have been the case in the other five species.…”
Section: Mirna Evolutionary Rates and Expression Levelsmentioning
confidence: 99%
“…Because they can regulate hundreds of target genes (Farh et al 2005;Lewis et al 2005), miRNAs have emerged as key modulators of gene function with links to human disease (Calin et al 2004;Jazdzewski et al 2009) and possible roles in phenotypic innovation (Heimberg et al 2008;Iwama et al 2013;Meunier et al 2013). miRNAs were first identified in the nematode Caenorhabditis elegans through cloning of mutations affecting temporal control of cell fate determination during larval development (Lee et al 1993;Reinhart et al 2000).…”
Section: Introductionmentioning
confidence: 99%